The spectrum of external dysmorphic features among newborns - O Sunil; M S Trinesh Gowda (Wolters Kluwer Medknow Publications, 2022)
Background: There is a frequent underreporting of minor congenital anomalies. The present study was conducted to identify and record the birth defects (external dysmorphism) among newborns delivered in district hospital attached to Mandya Institute of Medical Sciences, Mandya, for a duration of 1 year. Methodology: After obtaining the parent's written informed consent, newborns were examined for birth defects (visible external dysmorphic features). The details were recorded in the self-designed proforma, and findings/data were statistically studied. Birth defects were analyzed using the WHO International Classification of Diseases 10 reference guide. Results: During the present study, 502 live newborns were examined physically for external dysmorphic features and 17 cases were diagnosed as external congenital dysmorphism. In the present study, the frequency of congenital external dysmorphism was 3.4% and the most common system involved was a musculoskeletal system followed by cutaneous and central nervous system anomalies. We report five cases of talipes equinovarus, two cases of preauricular skin tags, one case each of polydactyly, syndactyly, harlequin ichthyosis, VACTERAL (vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, and limb abnormalities) association, Down syndrome, spina bifida cystica, spina bifida occulta, preauricular tags, preauricular sinus, cleft hard palate, and cleft lip with palate among other congenital anomalies noted. Conclusion: In the present study, the frequency of congenital external dysmorphism was 3.4% and the most common system involved was a musculoskeletal system (41.2%).